The Clustered Regularly Interspaced Short Palindromic Repeats-Associated System and Its Relationship With Mobile Genetic Elements in Klebsiella - Zhou, Yuqiao; Zhou, Wei; Zhou, Jinzhi; Yan, Jinchang; Xu, Dingting; Zheng, Xiner; Zong, Shuaizhou; Jiang, Ping; Tian, Shiyi; Han, Jianzhong; Qu, Daofeng (Frontiers in Microbiology, 2022)
Microorganisms have developed many strategies in the process of long-term defense against external attacks, one of which is the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated proteins (Cas) bacterial immunological system. In this study, the whole genome of 300 strains of Klebsiella was collected, the CRISPR-Cas system in the strains was statistically analyzed, and the types and structures of CRISPR system in Klebsiella were explored, as well as the correlation between CRISPR and mobile genetic elements (MGEs). Through principal component analysis (PCA), we found that Cas gene, plasmids, integron, IS1, IS609 and DNA-related enzymes were closely related to CRISPR. Compared the structural characteristics of plasmids, the DinG family helicases, Cas6, Csf2, and IS5 were observed near the CRISPR loci in plasmid, which is also confirmed by the the results of PCA that they may be important factors affecting the plasmid whith CRISPR.